Teacher`s Control on Students: Representation of Antisocial Communication in an Indonesian Language Learning Context - Sultan Sultan; Jufri Jufri (Bina Nusantara University, 2019)
This research examined teacher’s control of classroom interaction. Studying teachers’ controlling behaviors as a form of antisocial communication was necessary to develop teachers’ pedagogical competence and teacher-student relationships that were empowering and equitable. It employed a qualitative approach to critical discourse analysis. The respondents are six Indonesian Language teachers. Data collection was conducted by video recording, observation, and interview. Data were analyzed at the micro (text) and macro (social context) level. Research findings show that teacher’s control of classroom interaction might be realized in the acts of interrupting students, enforcing explicitness, controlling topic, formulating, restricting students’ contribution, asking close-ended questions, and ignoring students’ contribution. Teacher’s antisocial communication represented through various types of controls which can hinder the development of students’ language skills and adversely affect learning climates and students’ psychological aspects. Teacher’s beliefs and perspectives, teacher’s social status, and teacher’s pedagogical competence can be considered as factors that is able to contribute to practice of teacher’s control of students in classroom interaction.